Current challenges in interventional mitral valve treatment - Taramasso, Maurizio; Candreva, Alessandro; Pozzoli, Alberto; Guidotti, Andrea; Gaemperli, Oliver; Nietlispach, Fabian; Barthelmes, Jens; Emmert, Maximilian Y.; Weber, Alberto; Benussi, Stefano; Alfieri, Ottavio; Maisano, Francesco (Journal of Thoracic Disease, 2015)
Transcatheter mitral valve therapies have emerged as an alternative option in high surgical risk or inoperable patients with severe and symptomatic mitral regurgitation (MR). As multiple technologies and different approaches will become available in the field of mitral valve interventions, different challenges are emerging, both patient- (clinical challenges) and procedure-related (technical challenges). This review will briefly explore the current open challenges in the evolving fields of interventional mitral valve treatment.